Fuzzy evaluation of low carbon development levels for logistic enterprises in China - Peixin Zhao; Haoran Yu; Zhiyang Wang; Lulu Xu (Journal of Industrial Engineering and Management (JIEM), 2015)
Purpose: Under the background of global warming, low carbon economy, which is based on low waste and low pollution, has become a globally focused topic. Energy conservation, emission reduction and low carbon development have become irresistible trends of social development. A new set of low carbon evaluation index system for logistics enterprises is proposed. It is helpful for the better monitor of low carbon production and provide the optimization of industrial policies in China. Design/methodology/approach: Based on the problem that logistic analyses are facing under the background of low carbon economy, this paper firstly establishes a set of new evaluation indexes system, including 5 first-level indices and 28 second-level indices, for the low carbon development levels of logistics enterprises in China. To simplify the new evaluation system, the weight judgment method is then used to select indices, the validity judgment method and reliability coefficient judgment method are respectively used to test the validity and reliability of the evaluation systems. The simplified evaluation system consists of 4 first-class indices and 20 second-class indexes. Finally, numerical examples illustrate the validity and operability of the evaluation system. Findings: From the analysis and evaluation results, it is not difficult to obtain the rank of logistics enterprise according to the selected indexes or the overall evaluation indices. Low scores of some key indexes in strategy indices and technical indices cause low carbon emission performance. Moreover, The reason for the good low carbon performance of one enterprises is that it is in the lead on the key indexes of high weighs such as Perfection degree of low carbon development strategy, Level of transportation route optimization, etc. The new evaluation index system also helps enterprises to realize the sustainable development by identifying the key factors that affect the low carbon development level. Originality/value: The existing literature that assesses low carbon logistics is mostly focused on the review of the location-based and industry-based aspects, and little attention has been paid to assessing the efficiency of low carbon logistics from the components that are within the logistics enterprises. Therefore, we develop a new low carbon evaluation index system for logistics enterprises in order to better monitor low carbon production and provide the optimization of industrial policies in China.
Keywords: 650; clustering analysis; evaluation system; fuzzy evaluation; logistics; low carbon